The Role of Religious Fundamentalism in the Intersection of National and Religious Identities. (2019) - Wibisono, Susilo; Louis, Winnifred; Jetten, Jolanda
Indonesia has seen recent expansions of fundamentalist movements mobilising members in support a change to the current constitution. Against this background, two studies were conducted. In Study 1, we explored the intersection of religious and national identity among Indonesian Muslims quantitatively, and in Study 2, we qualitatively examined religious and national identification among members of moderate and fundamentalist religious organisations. Specifically, Study 1 ( N = 178) assessed whether the association of religious and national identity was moderated by religious fundamentalism. Results showed that strength of religious identification was positively associated with strength of national identification for both those high and low in fundamentalism. Using structured interviews and focus group discussions, Study 2 ( N = 35) examined the way that self-alignment with religious and national groups develops among activists of religious movements in Indonesia. We found that while more fundamentalist activists attached greater importance to their religious identity than to any other identity (e.g., national and ethnic), more moderate activists represented their religious and national identities as more integrated and compatible. We conclude that for Indonesian Muslims higher in religious fundamentalism, religious and national identities appear to be less integrated and this is consequential for the way in which collective agendas are pursued.